PREDICTIVE FACTORS AND CLINICAL AND PARACLINICAL FEATURES OF URINARY TRACT DYSFUNCTION IN PRETERM INFANTS - Ю. Годованець; А. Фрунза (Bukovynian State Medical University, 2023)
Acute kidney injury is a multifactorial clinical pathological syndrome that falls within the critical conditions of the early neonatal period and independently associates with high rates of morbidity and mortality. The frequency of acute kidney injury in critically ill preterm infants varies signifi cantly, ranging from 25 % to 77 % according to diff erent studies. Numerous scientifi c investigations describe an inversely proportional correlation between gestational age and birth weight. Of particular importance in terms of pathophysiology is the understanding of the concept of 'functional acute kidney injury,' clinically characterized by a reduction in glomerular fi ltration rate in the absence of markers of tubular damage. Consequently, it represents potentially reversible changes in renal function, sensitive to both the duration and depth of the alterations, which precede the development of injury. Aim of the study: To conduct an analysis of clinical characteristics, risk factors, and results of paraclinical examinations in preterm infants with gestational ages of 25-31 and 32-33 weeks, who exhibited signs of severe functional disturbances in the urinary system during the early neonatal period as part of complex perinatal pathology. Materials and Methods: A comprehensive clinical and paraclinical examination was conducted on 93 preterm infants with severe perinatal pathology. Group I comprised 30 infants with gestational ages of 25-31 weeks, while Group II consisted of 32 infants with gestational ages of 32-33 weeks. Group III included 31 conditionally healthy preterm infants with gestational ages of 34-36 weeks. Verifi cation of the diagnosis of renal dysfunction was performed according to the recommended international classifi cation 'Kidney Disease: Improving Global Outcomes' with the modifi cation by J. G. Jetton and D. J. Askenazi (2015). The degree of severity of polyorgan defi ciency in perinatal pathology in newborns was assessed using the Neonatal Multiple Organ Dysfunction Score. The eff ectiveness of therapeutic interventions was evaluated using the Neonatal Therapeutic Intervention Scoring scale. The severity of the newborns' condition during observation was assessed using the Score for Neonatal Acute Physiology scale. The research was conducted in accordance with the fundamental principles of Good Clinical Practice (GCP, 1996), the Council of Europe Convention on Human Rights and Biomedicine (April 4, 1997), the Helsinki Declaration of the World Medical Association on Ethical Principles for Medical Research Involving Human Subjects (1964-2008), as well as the Ministry of Health of Ukraine Order No. 690 dated September 23, 2009 (amended by the Ministry of Health of Ukraine Order No. 523 dated July 12, 2012). Statistical analysis of the obtained research results was performed using the software packages «Statistica 10» (StatSoft Inc., USA, 2010) and MedCalc Software (Version 16.1), with calculations including the odds ratio excess coeffi cient (Chi-squared), odds ratio (OR), and 95 % confi dence interval (CI). Statistically signifi cant diff erences between groups were considered at a signifi cance level of p < 0.005. The dissertation work was conducted within the scientifi c focus of the Department of Pediatrics, Neonatology, and Perinatal Medicine at Bukovinian State Medical University. The research themes included: a research project on 'Improvement of Prognostic, Diagnostic, and Therapeutic Approaches to Perinatal Pathology in Newborns and Infants, Optimization of Followup and Rehabilitation Schemes' (State registration number 0115U002768, duration from 01.2015 to 12.2019); and a research project on 'Chronobiological and Adaptive Aspects, as well as Features of Vegetative Regulation in Pathological Conditions in Children of Diff erent Age Groups' (State registration number 0122U002245, duration from 01.2020 to 12.2024). Research Results: The obtained results demonstrated statistically signifi cant associations between the severity of perinatal pathology in preterm infants and the depth of dysfunction in the urinary system, as well as a complex set of factors complicating the course of pregnancy and childbirth in mothers, thereby infl uencing the postnatal adaptation of the child. Among the reasons for complicated pregnancies, notable factors included anemia, cardiovascular and urinary system pathology, TORCH infections, isthmocervical insuffi ciency, disturbances in fetal- placental blood fl ow, the threat of spontaneous abortion, and premature labor. Anomalies such as abnormal fetal presentation, fetal distress, premature rupture of membranes, and urgent cesarean section were more likely to occur in women in this group. The course of perinatal pathology in newborns with gestational ages less than 33 weeks at birth was predominantly severe, with some children diagnosed with multiple organ dysfunction syndrome, one manifestation of which was acute kidney injury. Changes in the indicators of general and biochemical blood analysis in newborns refl ected low compensatory reserves of the neonatal organism in the context of experienced hypoxia and morpho- functional immaturity associated with premature birth. Conclusions: The formation of renal dysfunction in preterm infants in the early neonatal period has a complex polyetiological nature associated with a set of adverse factors during pregnancy and childbirth in mothers. Critically ill newborns represent a primary and challenging pediatric cohort in which this pathological syndrome is linked to high neonatal mortality rates and the development of functional and chronic pathology of the urinary system in later years, justifying the need for in-depth scientifi c research to consolidate perspectives on providing medical care to preterm infants.